METHOD OF ENCODING VIDEO SEGMENTS SIGNIFICANT IN TERMS OF IMPACT ON SEMANTIC INTEGRITY TO ENSURE ACCESSIBILITY - Barannik, Vladimir; Babenko, Yurii; Barannik, Valeriy; Kolesnyk , Vitalii (Science-based technologies, 2022)
Coding was created to increase the availability of video resources in conditions of ensuring the preservation of their semantic integrity based on segment typing and ensuing differentiated adaptive coding, taking into account the number of microsegments with different levels of SS saturation. The necessity of using jpeg family technological solution as a basic standardized platform is substantiated. This forms a conceptual platform for processing and building a format for presenting video resources to increase accessibility and integrity. In this direction, it is proposed in the process of standardized processing of video frames to additionally take into account the uneven distribution of the level of saturation of detailing information. At the same time, in order to reduce the number of arithmetic operations that additionally need to be spent on typing sections of the video frame, it is proposed to use structural and statistical (SS) properties of a nature based on the installation and parameterization of areas of permissible correction, including the area of slight change in the values of bright or colored components. Accordingly, the change in the level of saturation of the site with detailing information will manifest itself in an adequate change in the size of the CSF. The main stages for the development of a method of compact syntactic representation of segments of video frames, which are significant in their impact on the preservation of the RC VIR, and do not contain microsegments that have an insignified level of SS saturation, are provided and are given. It is shown that the reduction of bit volume is achieved on the basis of a reduction in the process of encoding the amount of redundancy of the following types: structural by limiting the maximum length of the LDC in the MSK; code in the presence of an extra number of older bits in the codegrams of significant components. The development of a method for identifying significant segments from the point of view of preserving semantic integrity of video resources on the basis of using a system of rules for deciding on information on structural and statistical properties of microsegments belonging to the bright component of the colour and difference representation of the video frame is laid out.